Analysis Strategy and Parametric Study of Cable-Stayed-Suspension Bridges. Issue 6 (June 2013) - Sun, Bin; Cai, C.S.; Xiao, Rucheng
This paper presents a systematic analysis strategy for cable-stayed-suspension bridges. A four-step approach for the determination of the reasonable finished dead load state is established, focusing on the optimization of the tension forces and shapes of all cables. The critical distribution of the traffic load is imposed on the bridge simultaneously with the dead load to calculate its nonlinear effect. Taking the finished dead load state as the initial state, the nonlinear effect of each load in the service state is analyzed independently. The superimposition principle is adopted to obtain the load combination. A 1400 m span cable-stayed-suspension bridge is presented as a case study. Finally, three key geometric parameters are studied from the viewpoint of the structural behavior. As a result, a suspension-to-span ratio of 0.4 to 0.6, a larger sag-to-span ratio up to 1/11.0, and two to four crossing hangers are recommended. With a higher structural rigidity and stability, this type of bridge is proven as an excellent alternative to cable-stayed bridges and suspension bridges.